Experivivências (auto)etnográficas: artista-professora e estudantes de uma escola pública em Maracanaú/CE - Moreira, Silmara Peixoto (2021)
This paper is based on the experience of the researcher as an artist-teacher of a Visual Arts elective in a full-time public state school, located in Maracanaú-CE. It is understood that anthropology plays an important role in the process of questioning paradigms in the field of education, broadening the context to be investigated, especially regarding the dialogue between art and education. In this fieldwork process, we conceptualize as autoethnographic experiences, the way of doing research based on the experiences of the researcher herself. One of the goals of this research was to identify how artistic expressions are part of the social experiences of the student-artists and in what way the artistic production of student-artists is allied to their social context inside and outside of school. In this work we established several dialogues with different social agents, in particular with four young student-artists. This methodology of experiviences finds theoretical grounding in Mariza Peirano "teoriavivida" (1995; 2006), in the reflection of "autoethnography" brought by Strathern, (2014), in "affect in anthropology" brought by Jeanne Favret-Saada (2005), in the feminist writing of Donna Haraway (2004), and of Bell Hooks (2015), and in Paulo Freire education as transformative practice (1980; 2015). The methodology of experivivences consists in the relationship of approaching the interlocutors in the fieldwork not only by describing and observing it, but by relating, feeling it, living it, and experiencing it with the social groups, embodied and contextualized historically, in time and space, with all the complexity of social and interpersonal relationships. The experiences are also found in the approximation of several axes of differentiation of social markers, (of class, race/color, ethnicity, gender, and sexuality) and the ways they relate to each other in the school context and outside it.